2012
DOI: 10.1007/s10503-012-9284-5
|View full text |Cite
|
Sign up to set email alerts
|

What Students’ Arguments Can Tell Us: Using Argumentation Schemes in Science Education

Abstract: The role of argumentation in science education has been stressed by a growing literature that emphasized the problem of constructing students' knowledge taking into account their previous beliefs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Walton's reasoning scheme is interpreted based on context, subjects, and topics (Nussbaum, 2011). Reasoning scheme such as correlation to cause and cause to effect are more often used in the context of science education than other discipline (Macagno & Konstantinidou, 2013). For example, in a study conducted by Nussbaum and Edwards (2011), found six reasoning schemes when students engaged in global warming issues.…”
Section: Assessing Collaborative Scientific Reasoning Patternsmentioning
confidence: 99%
“…Walton's reasoning scheme is interpreted based on context, subjects, and topics (Nussbaum, 2011). Reasoning scheme such as correlation to cause and cause to effect are more often used in the context of science education than other discipline (Macagno & Konstantinidou, 2013). For example, in a study conducted by Nussbaum and Edwards (2011), found six reasoning schemes when students engaged in global warming issues.…”
Section: Assessing Collaborative Scientific Reasoning Patternsmentioning
confidence: 99%
“…Rick has fair skin, red hair and freckles, and he sunbathed the whole day. Because of its form-focusing nature, this framework has been mainly used for assessing students' written arguments (Macagno & Konstantinidou, 2013;, but with various concerns and limitations (Rapanta et al, 2013;. Its application to classroom oral discourse is described by Erduran et al (2004), but it has never been extensively used for this latter purpose.…”
Section: Data (Premise) Claimmentioning
confidence: 99%
“…Argumentation schemes theory The last framework underlying several approaches to the assessment of the quality of argumentative texts is argumentation schemes theory (Anthony & Kim, 2015;Macagno & Konstantinidou, 2013;Metaxas, Potari, & Zachariades, 2016;Nussbaum, 2003Nussbaum, , 2008). Walton's theory of argumentation schemes (Walton, 1995;Walton, Reed, & Macagno, 2008) is focused on the analysis and classification of Toulmin's warrants (Toulmin, Rieke, & Janik, 1984).…”
Section: Second-order Evidencementioning
confidence: 99%
“…In reviewing Toulmin's framework, Kim and Roth (this issue) provide a series of criticisms to highlight why TAP is not suitable as a framework for their purposes of identifying social relational aspects of argumentation. For example, they cite that TAP (a) is linear and technical when adapted as a sole analytical framework in research (Macagno and Konstantinidou 2013); (b) presented difficulties in the ambiguity of coding schemes (Kelly and Takao 2002); (c) proved to be problematic for analyzing students' argumentation encountering difficulties in coding between data and warrants and warrants and backings (Erduran, Simon, Osborne 2004); (d) does not sufficiently explain the dynamics of epistemic and social criteria of argumentation (Nussbaum 2011). Simply coding students' argumentation with TAP schemes makes it a challenge to understand the criteria of claim acceptance or rejection, implicit premises and standpoints, and the dynamics of social interactions and presumption that are often present in argumentative discussions (Nielsen 2013).…”
Section: Critique Of Toulmin's Argument Pattern: Is It Justified?mentioning
confidence: 99%